Marginally deformed AdS 5 /CFT 4 backgrounds in Type IIB - PAUL MERRIKIN (Journal of High Energy Physics, 2024)
Multi-parameter families of N = 0 Type IIA and Type IIB AdS5 solutions are presented, promoting to N = 1 in some special cases. The G-Structure description of each N = 1 solution is given, requiring an Abelian T-Duality of the G-Structure conditions and Pure Spinors. Investigations at the boundaries are performed for a two-parameter family of Type IIA and a three-parameter family of Type IIB solutions, finding the presence of orbifold singularities in some backgrounds. All parameters drop out of the Holographic Central Charge calculation, pointing to marginal deformations in the dual CFT description.